“Proud, rebel, political”: How Maradona influenced football governance - Agafonova, Rusa (Eracle. Journal of Sport and Social Sciences, 2022)
It is difficult to put the phenomenon of Diego Armando Maradona into legal terms. Nevertheless, Maradona contributed to the economic and political landscapes of football as we know them today. The Argentinian legend played an enormous role in popularising football on a global scale and made it a part of popular culture. Maradona was also known for his turbulent relations with football governing bodies, notably with the FIFA, the international football federation. On some occasions he acted as FIFA’s ambassador, on others he criticised the organisation harshly. In this article, the author wants to revisit Maradona’s style of making political statements and his manner to interact with sports organisations in order to understand whether his personality would fit modern sports regulatory framework and which lessons can be drawn from his approach by athletes and by governing bodies.